2009
DOI: 10.1007/s12013-009-9052-9
|View full text |Cite
|
Sign up to set email alerts
|

The R7 RGS Protein Family: Multi-Subunit Regulators of Neuronal G Protein Signaling

Abstract: G protein-coupled receptor (GPCR) signaling pathways mediate the transmission of signals from the extracellular environment to the generation of cellular responses, a process that is critically important for neurons and neurotransmitter action. The ability to promptly respond to rapidly changing stimulation requires timely inactivation of G proteins, a process controlled by a family of specialized proteins known as regulators of G protein signaling (RGS). The R7 group of RGS proteins (R7 RGS) has received spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
151
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 145 publications
(241 reference statements)
4
151
2
Order By: Relevance
“…(Holden et al , 2014; Kach et al , 2012). In particular, RGS7 plays key roles in the regulation of several biological processes such as vision, memory, motor control, reward behavior and nociception (Anderson et al , 2009; Orlandi et al , 2015). Although the mechanisms of this regulation remain to be elucidated, we demonstrated that long‐term administration of 3 mg/kg of WIN during mouse adolescence induces DNA hypermethylation at the intragenic Rgs7 region and concomitantly decreases the rate of transcription, potentially contributing at least in part to the learning and memory deficits as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(Holden et al , 2014; Kach et al , 2012). In particular, RGS7 plays key roles in the regulation of several biological processes such as vision, memory, motor control, reward behavior and nociception (Anderson et al , 2009; Orlandi et al , 2015). Although the mechanisms of this regulation remain to be elucidated, we demonstrated that long‐term administration of 3 mg/kg of WIN during mouse adolescence induces DNA hypermethylation at the intragenic Rgs7 region and concomitantly decreases the rate of transcription, potentially contributing at least in part to the learning and memory deficits as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional domains unique to R7 family members, the GGL (G␥ subunit-like) domain and DEP/ DHEX domain, allow for complex formation between RGS6 and the accessory proteins G␤ 5 and R7BP, respectively. Binding to G␤ 5 results in stabilization of both proteins, whereas binding to R7BP is thought to primarily control the subcellular localization of R7 family members (18). R7 family RGS proteins have been implicated in controlling motor movement, because G␤ 5 Ϫ/Ϫ mice, which lack functional expression of all R7 family members (19), exhibit an ataxic phenotype likely due to abnormal cerebellar development (20,21).…”
mentioning
confidence: 99%
“…This GTPase rate is determined by a complex of proteins that include T␣*-GTP, RGS9 -1, and other proteins (33); P␥ serves to facilitate the formation of a tighter complex of these proteins to potentiate the GTPase accelerating function of RGS9 -1 (34 -37). However, the interaction surface of P␥ with RGS9 -1 and the functional significance of the interactions are unclear.…”
mentioning
confidence: 99%